Sun-as-a-star variability of Hα and Ca II 854.2 nm lines - Zills, Garrett; Criscuoli, Serena; Bertello, Luca; Pevtsov, Alexei (Frontiers in Astronomy and Space Sciences, 2024)
Studies of stellar magnetic fields mostly rely on proxies derived from chromospheric lines, typically forming in the UV and shorter wavelengths and therefore accessible only from space based observatories. Even Ca II K or H observations, forming in regions accessible from the ground, are not always available. As a result, there is a crucial need to explore alternative activity proxies to overcome the limitations posed by observational constraints. Using sun-as-a-star observations acquired with the ISS at SOLIS we investigated the correlation between the Ca II K emission index and indices derived from the Hα 656.3 nm and Ca II 854.2 nm lines, which are well known chromospheric diagnostics. We found that both the core intensities and widths of the two lines are positively correlated with the Ca II K emission index (ρ ≳ 0.8), indicating their suitability as reliable indicators of magnetic activity, the width of the Hα line showing the highest correlation (ρ =0.9). We also found that such correlations vary with the activity cycle. Specifically, during the analyzed cycle 24, the correlations with the Ca II K index varied 14% for the Hα width, 33% for the Hα core intensity, and doubled for the two Ca II 854.2 nm line indices. These results suggest that, among the investigated indices, the Hα width best traces magnetic activity. Results are discussed at the light of current knowledge of the formation heights of the two lines, and of spatially resolved solar observations.